Periostin and transforming growth factor β‐induced protein (TGFβIp) are both expressed by osteoblasts and osteoclasts. (31st December 2013) - Merle, Blandine; Bouet, Guenaelle; Rousseau, Jean‐Charles; Bertholon, Cindy; Garnero, Patrick
Abstract Periostin (Postn) and transforming growth factor β‐induced protein (TGFβIp) are two closely related extracellular matrix (ECM) proteins predominantly distributed in collagen‐rich connective tissues submitted to mechanical strain, including bone and more specifically the periosteum. We have investigated the expression of Postn and TGFβIp mRNA by primary osteoblasts isolated from mouse periosteum and calvaria, or by the osteoblast‐like MC3T3‐E1 cell line, and by osteoclasts from mouse long bones differentiated in vitro. Secretion of Postn was measured with a specific ELISA. Postn and TGFβIp mRNA were concomitantly expressed in all three osteoblast models all along the differentiation process in a time‐dependent manner. Both Postn and TGFβIp transcripts appeared early in osteoblast differentiation, and their expression increased 3–10 times in mature osteoblast cells. Expression decreased after differentiation was achieved and when the cultures mineralised. ELISA for secreted Postn showed a similar pattern. When MC3T3‐E1 cells were treated with TGF‐β, Postn and TGFβIp mRNA expression and secretion were stimulated, whereas 1.25(OH)2D3 had no detectable effect. Osteoclasts also expressed both Postn and TGFβIp during in vitro differentiation. Expression of both Postn and TGFβIp peaks in the early phases of osteoblast differentiation, and decreases later at the start of mineralisation. A novel finding is that Postn and TGFβIp are expressed by osteoclasts in vitro. Therefore Postn and TGFβIp proteins are potential biomarkers of early osteoblast differentiation and new bone formation.